Implementação de um regime centralizador de matrícula por disciplina numa instituição particular de ensino superior - Vasconcellos, Isac João de (1982)
The purpose of this study was to analyse the implementation of a Centralized Regime of Student Enrollment by Discipline at Faculdades Integradas Simonsen. It intended, through a Centralized Regime, to eliminate the problems involved in the application, in Brazilian institutions of college level, of the Regime of Enrollment by Discipline according to foreign models.